The PHD transcription factor Cti6 is involved in the fungal colonization and aflatoxin B1 biological synthesis of Aspergillus flavus - Zhang Mengjuan; Lin Guanglan; Pan Xiaohua; Song Weitao; Tan Can; Chen Xuan; Yang Yanling; Zhuang Zhenhong (IMA Fungus)
Abstract Aspergillus flavus and its main secondary metabolite AFB1 pose a serious threat to several important crops worldwide. Recently, it has been reported that some PHD family transcription factors are involved in the morphogenesis and AFB1 biological synthesis in A. flavus, but the role of Cti6, a PHD domain containing protein in A. flavus, is totally unknown. The study was designed to reveal the biological function of Cti6 in the fungus by deletion of cti6, and its two domains (PHD and Atrophin-1) through homologous recombination, respectively. The results showed that Cti6 might up-regulate the mycelium growth, conidiation, sclerotia formation and AFB1 biological synthesis of A. flavus by its PHD domain, while Atrophin-1 also improved the conidiation of the fungus. The qRT-PCR analysis showed that Cti6 increased the conidiation of the fungus through AbaA and BrlA mediated conidiation pathway, triggered the formation of sclerotia by orthodox sclerotia formation pathway, and improved the production of AFB1 by orthodox AFB1 synthesis pathway. Crops models analysis showed that A. flavus Cti6 plays vital role in colonization and the production of AFB1 on the host grains mainly via PHD domain. Bioinformatics analysis showed Cti6 is conservative in Aspergillus spp., and mCherry mediated subcellular localization showed that most Cti6 accumulated in the nuclei, which reflected that Cti6 performed its important biological function in the nuclei in Aspergillus spp.. The results of the current study elucidate the roles of PHD domain containing proteins in the mechanism of the infection of crops by A. flavus, and provided a novel target for effectively controlling the contamination of Aspergillus spp. to crops.